الإبداع القرآني في كشف أساليب اليهود السياسية في تزييف الوعي والتلاعب بالعقول (The Qur’anic Creativity in Revealing Jewish Political Methods of Falsifying Consciousness and) - زرؤم عبد الحميد محمد علي; عبد السلام الفاتح عبد الله (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص على مدار التاريخ الإنساني، ارتبط اسم اليهود بالفتن والاضطرابات، وظلت سمة الدسائس والمكائد، وحب السيطرة ملازمة لهم في حلهم وترحالهم حتى يومنا هذا، ولا تتورع قياداتهم السياسية والفكرية أن تبوح بذلك جهرا بين الفينة والأخرى من خلال وسائل الإعلام المقروءة والمكتوبة والمسموعة والمرئية، ومن خلال الكتابات والمنشورات التي تؤصل لفكرة "شعب الله المختار" وفي سبيل تحقيق هذه الفكرة، استخدموا ومايزالون كل الوسائل المشروعة والممنوعة. وقد أبدع القرآن الكريم في عرض حقيقة التضليل الإعلامي الذي كان يقوم به اليهود لاسيما في عهد النبي صلى الله عليه وسلم، وفترة احتكاك بني قريظة وبني النضير وبني قينقاع بالمسلمين في المدينة احتكاكا مباشرا. هذه الدراسة تلقي الضوء على الإبداع القرآني في كشف الحيل والأساليب السياسية التي مارسها اليهود في محاولاتهم المستميتة في تزييف الوعي والتلاعب بالعقول. للوصول إلى النتائج التي ينشد الباحث تحقيقها، تم في هذه الدراسة المقتضبة استخدام المنهجين التحليلي، والتاريخي الاستردادي. ومن أهم ما توصلت إليه الدراسة أن القرآن المجيد كشف الأدوار التخريبية التي يلعبها اليهود، ومواقفهم المخزية، والحرب النفسية التي كانوا يمارسونها ضدّ الرسول صلى الله عليه وسلم ودعوته من خلال إثارة الشكوك، ونشر الشائعات، وحرب الجدل العقيم، والأسئلة التعجيزية، وعرضها بأسلوب تجلى فيه الإبداع والإثارة والتشويق. الكلمات المفتاحية: الإبداع، القرآن، اليهود، السياسة، تزييف الوعي، التلاعب بالعقول. Abstract Throughout human history, the name of Jews was associated with predicaments and disorder. Intrigues, plots and the love of control have accompanied them in their settlings and nomadic life style till the very day. The Jewish political and intellectual leaders do not refrain from revealing such features through social media, publications, and leaflets that aim to establish the idea that they are God’s chosen people. To achieve this, the Jews have used and still use all legal and illegal means. The Holy Quran had excelled in describing the reality of informative deception used by the Jews especially in the time of Prophet Muhammad (s.a.w.) and the direct contact of BanÊ Qurayẓah, BanÊ al-NaḍÊr and Bani QainuqÉʿ with Muslims in Medina. This study investigates the Quranic creativity in exposing deceptive and political methods used by the Jews in their deadly efforts to falsify consciousness and manipulate minds. The researcher utilizes the analytical and historical retrieval methods in this brief study. Amongst the important findings of this work is: The Quran revealed the destructive roles played by the Jews. It unveiled their blatant attitudes and the psychological war they waged against Prophet Muhammad (s.a.w.) and his mission (daʿwah) through hovering suspicions, spreading rumours, waging wars of futile argument and unreasonable questions. All these are exposed in a creative, exciting and suspenseful method. Keywords: Creativity, the Quran, Jews, politics, falsifying consciousness, manipulating Minds.